Effect of Reaction Time and Temperature on Biodiesel Production from Vegetable Oil - ABU BAKAR, ASYIQ; Main, Nor Mazlana; Nasir, Nurul Fitriah (Research Progress in Mechanical and Manufacturing Engineering, 2024)
An alternative fuel made from renewable resources such as leftover cooking oil, vegetable oils, and animal fats is called biodiesel. With the world’s population growing and the need for diesel fuel rising, the search for alternative fuels is becoming increasingly important. The process used in this study’s experiment is turning corn oil into biodiesel. Sodium hydroxide (NaOH) was chosen as the catalyst, and methanol was utilised as the alcohol. This project aims to analyze the properties blended in biodiesel, such as yield percentages, density, kinetic viscosity, and F-TIR spectrum, according to different conditions of reaction time and reaction temperature. Reaction time took 1 and 2 hours through different temperatures, 50 °C and 60 °C to produce 4 samples each. Ingredients to make analyzed biodiesel in this experiment were 400 ml of corn oil, 101.97 ml of methanol, and 2.79 g of sodium hydroxide (NaOH). 4 samples were produced in analysis determination. Sample 1 was done under 1 h and 50 °C, sample 2 was done under 1 h and 60 °C, while sample 4 was done under 2 h and 50 °C. Lastly, sample 4 was done under 2 h and 60 °C. The best result sample biodiesel yield was sample 3 out of all samples produced using a 2-hour reaction time at 50 °C. In the meantime, the density of each sample produced is about the same, and the kinematic viscosity increases with temperature over the course of two hours of reaction time. Consequently, it is discovered that as the temperature rises, the yield decreases with each reaction time. The best sample in terms of kinetic viscosity is sample 1. Nonetheless, the goal of producing a percentage of biodiesel production between 72% and 75% was accomplished. Hence, this study can improve renewable energy with less hydrocarbon emissions for a healthy future.